2021
DOI: 10.1186/s12944-021-01568-9
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio, an optimal anthropometric indicator for metabolic dysfunction associated fatty liver disease in the Western Chinese male population

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) has been entitled as metabolic-dysfunction associated fatty liver disease (MAFLD). Therefore anthropometric indicators of adiposity may provide a non-invasive predictive and diagnostic tool for this disease. This study intended to validate and compare the MAFLD predictive and diagnostic capability of eight anthropometric indicators. Methods The study involved a population-based retrospective cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
0
18
1
Order By: Relevance
“…31 Additionally, studies also indicated that WHR and WHtR had been suggested as most useful predictor of MAFLD only in relatively young Chinese males; Furthermore, BAI represents the overall adipose accumulation and does not reflect the characteristics of abdominal fat accumulation. Although previous studies demonstrated the relative association of BMI and BAI with fatty liver disease, 30 the diagnostic performance of both BMI and BAI was inferior compared to the other visceral obesity indices in the early postmenopausal women. Furthermore, characteristics such as sex, age or ethnicity can influence the prediction of MAFLD.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…31 Additionally, studies also indicated that WHR and WHtR had been suggested as most useful predictor of MAFLD only in relatively young Chinese males; Furthermore, BAI represents the overall adipose accumulation and does not reflect the characteristics of abdominal fat accumulation. Although previous studies demonstrated the relative association of BMI and BAI with fatty liver disease, 30 the diagnostic performance of both BMI and BAI was inferior compared to the other visceral obesity indices in the early postmenopausal women. Furthermore, characteristics such as sex, age or ethnicity can influence the prediction of MAFLD.…”
mentioning
confidence: 69%
“…Moreover, the AUC of BMI in subgroup analysis was greater than 0.8, and represented its good predictive performance in most populations. 30 However, previous study had not explored its predictive value of MAFLD among early postmenopausal women, and BMI may not reflect the abdominal adipose tissue accumulation among women after menopause. Besides, the validity of BMI as a valuable indicator of regional adipose distribution remains controversial because of its inability to distinguish between fat mass and lean body mass.…”
mentioning
confidence: 99%
“…The accumulation of visceral fat was regarded as a key risk factor and predictor of NAFLD ( 33 , 34 ). Excessive visceral adipose tissue may result in lipotoxicity, insulin resistance and the increase of pro-inflammatory mediators ( 35 ). An increase in interleukin-6, C-reactive protein, interleukin-1β, and tumor necrosis factor-α was found in the population of MAFLD ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the TG/HDL-C was confirmed as the predictor of nonalcoholic fatty liver disease, and it can identify insulin resistance, abdominal obesity, metabolic disorders, and cardiometabolic risk (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The WHtR was identified as an optimal anthropometric indicator for MAFLD in the Western Chinese male population (17).…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that MAFLD was closely related to body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), aminotransferase, fatty acid, serum levels of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and the ratio of TG and HDL-C (TG/HDL-C) (17)(18)(19)(20). Among them, the TG/HDL-C was confirmed as the predictor of nonalcoholic fatty liver disease, and it can identify insulin resistance, abdominal obesity, metabolic disorders, and cardiometabolic risk (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The WHtR was identified as an optimal anthropometric indicator for MAFLD in the Western Chinese male population (17).…”
Section: Introductionmentioning
confidence: 99%